Vulvar salmon patch. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
The three baby girls here reported presented since birth erythematous patches of the vulvar region, uni- or bilaterally, asymptomatic, that disappeared with the pressure of the fingers and did not grow in the first weeks of life. The absence of coarse telangiectases and proliferative papules led us to exclude the diagnosis of precursor of infantile hemangioma. The limited extent of the lesions led us rule out a capillary malformation as port-wine stain. The presence in all three cases of typical salmon patches in the frontal and nuchal region, in the third case of salmon patches of the back and in the first case of the occipital region, leads us to consider probable the diagnosis of salmon patch, although this vulvar localization of salmon patch is not reported in the Books of Dermatology (1), nor in the literature (2-12).